How big are effect sizes in international education studies? - Evans, David; Yuan, Fei (Center for Global Development, 2020)
In recent years, a growing literature has measured the impact of education interventions in low- and middle-income countries on both access and learning outcomes. But interpretation of those effect sizes as large or small tends to rely on benchmarks developed by a psychologist in the United States in the 1960s. In this paper, we demonstrate the distribution of standardized effect sizes on learning and access from hundreds of studies from low- and middle-income countries.

Equivalent Years of Schooling: A Metric to Communicate Learning Gains in Concrete Terms - Evans, David K; Yuan, Fei (World Bank Policy Research, 2019)
In the past decade, hundreds of impact evaluation studies have measured the learning outcomes of education interventions in developing countries. The impact magnitudes are often reported in terms of "standard deviations," making them difficult to communicate to policy makers beyond education specialists. This paper proposes two approaches to demonstrate the effectiveness of learning interventions, one in "equivalent years of schooling" and another in the net present value of potential increased lifetime earnings. The results show that in a sample of low- and middle-income countries, one standard deviation gain in literacy skill is associated with between 4.7 and 6.8 additional years of schooling, depending on the estimation method. In other words, over the course of a business-as-usual school year, students learn between 0.15 and 0.21 standard deviation of literacy ability. Using that metric to translate the impact of interventions, a median structured pedagogy intervention increases learning by the equivalent of between 0.6 and 0.9 year of business-as-usual schooling. The results further show that even modest gains in standard deviations of learning -- if sustained over time -- may have sizeable impacts on individual earnings and poverty reduction, and that conversion into a non-education metric should help policy makers and non-specialists better understand the potential benefits of increased learning.
Keywords: Education; Impact Evaluation; Learning Outcomes; Lifetime Earnings; Net Present Value; Poverty Reduction; Years of Schooling; ___working_potential_duplicate

What We Learn about Girls’ Education from Interventions That Do Not Focus on Girls | The World Bank Economic Review | Oxford Academic - Evans, David K; Yuan, Fei (2022)

Equivalent Years of Schooling: A Metric to Communicate Learning Gains in Concrete Terms - Evans, David K.; Yuan, Fei (2019)
In the past decade, hundreds of impact evaluation studies have measured the learning outcomes of education interventions in developing countries. The impact magnitudes are often reported in terms of "standard deviations," making them difficult to communicate to policy makers beyond education specialists. This paper proposes two approaches to demonstrate the effectiveness of learning interventions, one in "equivalent years of schooling" and another in the net present value of potential increased lifetime earnings. The results show that in a sample of low- and middle-income countries, one standard deviation gain in literacy skill is associated with between 4.7 and 6.8 additional years of schooling, depending on the estimation method. In other words, over the course of a business-as-usual school year, students learn between 0.15 and 0.21 standard deviation of literacy ability. Using that metric to translate the impact of interventions, a median structured pedagogy intervention increases learning by the equivalent of between 0.6 and 0.9 year of business-as-usual schooling. The results further show that even modest gains in standard deviations of learning -- if sustained over time -- may have sizeable impacts on individual earnings and poverty reduction, and that conversion into a non-education metric should help policy makers and non-specialists better understand the potential benefits of increased learning.